THE URGENCY OF DA'WAH MANAGEMENT OF NAHDLATUL ULAMA (PCNU) BRANCH MANAGEMENT IN BONE REGENCY - Sri Nuraini; Nilna Indriani; qudratullah; Wandi (Palakka : Media and Islamic Communication, 2026)
This study aims to analyze the implementation of da'wah management by the Nahdlatul Ulama Branch Leadership (PCNU) of Bone Regency from the perspective of Hersey and Blanchard's Situational Leadership Theory. This study is motivated by the need for da'wah organizations to adapt to social dynamics and technological developments in the modern era. The novelty of this research lies in the examination of da'wah management based on situational leadership at the branch level of a religious organization through a local contextual approach, which is still rarely studied. This study uses a qualitative case study approach. Data were collected through in-depth interviews, observations, and documentation involving five informants consisting of the chairman, secretary, and administrators of PCNU Bone Regency. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing, with validity tested through source triangulation. The results of the study show that the functions of da'wah management planning, organizing, implementing, and evaluating are applied systematically through structural and cultural channels. The implementation of situational leadership is reflected in the flexibility of leadership styles adjusted to the conditions and readiness levels of members. This study contributes to strengthening the da'wah management model based on situational leadership as a strategy for managing local-level da'wah organizations in an adaptive and contextual manner.